2015
DOI: 10.1155/2015/908315
|View full text |Cite
|
Sign up to set email alerts
|

Enabling Cyber Physical Systems with Wireless Sensor Networking Technologies, Multiagent System Paradigm, and Natural Ecosystems

Abstract: Wireless sensor networks (WSNs) are key components in the emergent cyber physical systems (CPSs). They may include hundreds of spatially distributed sensors which interact to solve complex tasks going beyond their individual capabilities. Due to the limited capabilities of sensors, sensor actions cannot meet CPS requirements while controlling and coordinating the operations of physical and engineered systems. To overcome these constraints, we explore the ecosystem metaphor for WSNs with the aim of taking advan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 34 publications
(45 reference statements)
0
6
0
1
Order By: Relevance
“…Os três principais objetivos são: agregar dados para o sensoriamento tornar-se mais barato, otimização de hardware e auto-adaptações preditivas. O trabalho de [Jabeur et al 2015] propõe modelos para redes de sensores sem fio baseadas em aspectos da natureza e são chamados de bio-inspirados. Nele, a rede formada pelos nós sensoresé descrita como análoga a um ecossistema.…”
Section: Trabalhos Relacionadosunclassified
“…Os três principais objetivos são: agregar dados para o sensoriamento tornar-se mais barato, otimização de hardware e auto-adaptações preditivas. O trabalho de [Jabeur et al 2015] propõe modelos para redes de sensores sem fio baseadas em aspectos da natureza e são chamados de bio-inspirados. Nele, a rede formada pelos nós sensoresé descrita como análoga a um ecossistema.…”
Section: Trabalhos Relacionadosunclassified
“… Complex Networked Organizational Design. According to the network organizational paradigm, modern cyber-physical systems that are oriented to the lean management of Industry 4.0 can be seen as a socio-technical symbiotic ecosystem of human networks [ 5 ] interacting with distributed physical sensors interconnected in an increasingly complex network interconnected sensors [ 48 ], which readings are modeled as time-dependent signals at the vertices, human, or cyber-physical, respectively. That means that in the structure of the network nodes you can find characteristics that represent them in the form of a certain time series that describes the key performance indicators (KPIs).…”
Section: Introductionmentioning
confidence: 99%
“…• Complex-Networked Organizational Design. Under the organizational-network paradigm, modern Industry 4.0 cyber-physical lean-management-oriented organizations can be understood as a symbiotic sociotechnical ecosystem of social networks [16] that interacts with increasingly complex-networked physically distributed interconnected sensors [17], whose readings are modeled as time-dependent signals on the vertices, human or cyber-physical, respectively. This means that, on the nodes of the network, attributes can be found that describe them as having the form of a given time series.…”
Section: Introductionmentioning
confidence: 99%